ESRU Model in ESP Context: Insight from EFL Teacher’s Practice - Milawati - Milawati; Nurir Rohmah; Helmy Sahirul Alim (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
To carry out formative assessments, the ESRU model is used to analyze all utterances indicated as teachers' strategies in implementing informal formative assessments. The ESRU model begins with the initiation of the teacher in asking questions to generate student thoughts, then the students provide responses to the teacher's initiation questions. Furthermore, student responses can be recognized by teachers and teachers provide feedback on student responses. A case study on ESP classes was observed to investigate in depth information dealing with the ESRU Model implementation. It revealed that teacher-students interaction was dominantly occured, teacher can use information to support learning and modify their learning to help students achieve learning targets that are determined together. Thus the existing gap can be minimized, both students and teachers can benefit from the information obtained from informal formative assessments.